Anchored Double-Tier Retaining Walls on Sloping Embankment - Chu E. Ho; Paul Napoli (Deep Foundations Institute, 2019)
A new waterfront park was developed on Long Island in close proximity to the East River and Newtown Creek. The existing ground consisted of fill over soft organic clay, medium dense silty sand, glacial till and schist bedrock. The ground was initially raised to preload the underlying soft soils to stabilize the ground in preparation for site development. The ground was subsequently cut down to temporary grades for installation of foundation piles for the overlook structures and construction of reinforced concrete cantilever retaining walls forming pathways located adjacent to the water bodies. The retaining walls were located in two rows at different elevations along the sides of a steep embankment. Where the pathways converge, some of the walls were too close to each other, and were redesigned as a combined U-wall with a common base slab. The individual retaining walls were designed for adequate bearing, sliding and overturning resistance. Ground anchors were installed to enhance global stability of the retaining walls. This paper presents the design considerations for the retaining walls for various loading conditions, and evaluation of the trial and proof tests for the anchors. INTRODUCTION The New York City Master Plan included the transformation of an approximately 30-acre parcel of land in Long Island City, Queens, New York from a former manufacturing zone into a residential, commercial and recreational zone for middle-income community. The site was located at Hunters Point South along the eastern shoreline of the East River and Newtown Creek (Figure 1). The development included low to high- rise residential buildings, a public school, and retail structures. Open spaces were provided along the East River and Newtown Creek waterfronts in the form of a continuous park providing for recreational and community-related activities. Waterfront structures included small park buildings, walkways and viewing platforms. The shoreline was surrounded by revetments as part of the flood mitigation strategy. The project involved extensive site re-grading and several retaining walls were constructed. The earthwork volume amounted to approximately 47,000 cubic yard of imported fill and 93,000 cubic yard of cut. The exposed height of the retaining walls ranged from 3 to 15 feet. This paper focuses on the design and construction of the retaining walls for the project.